DAMPAK PEMBELAJARAN SEJARAH PENDIDIKAN ISLAM BERBASIS E-LEARNING TERHADAP KEMANDIRIAN BELAJAR MAHASISWA - fauzi agustia lestari; Undang Ruslan Wahyudin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
E-learning is a much needed thing especially in the history of Islamic education so it can trigger a level of independence in every student by using various online facilities that can be accessed by anyone, anywhere, and anywhere. Without an e-learning-based learning model, students lack the flexibility or initiative to learn especially in the eyes of Islamic education history that requires the focus to read and understand the course of events that are very important to know. The purpose of this research is to find out what impact the study of Islamic education history has on the student's independence. The approach that researchers use in this research is a qualitative approach to descriptive analysis. This research suggests that the study of Islamic education history based on e-learning can impact on student independence, and with the various strategies and efforts made by the Islamic education history professor to e-learning also provides opportunities, rankings.The ambition of independence in studying with every student well.